1998
DOI: 10.1007/s002030050679
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of cobalamin in Salmonella typhimurium : transformation of riboflavin into the 5,6-dimethylbenzimidazole moiety

Abstract: In order to elucidate the biosynthesis of the base moiety of cobalamin in Salmonella typhimurium LT2, this organism was grown in the presence of [1'-14C]riboflavin. The vitamin B12 isolated was 14C-labeled. It was shown by chemical degradation that the 14C-label was exclusively localized in carbon atom 2 of the 5,6-dimethylbenzimidazole moiety. This demonstrated the precursor function of riboflavin in the biosynthesis of 5,6-dimethylbenzimidazole in S. typhimurium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…It was reported that wild-type S. enterica synthesizes pseudo-B 12 during growth under strictly anaerobic conditions and standard B 12 under microaerobic conditions (21,22). Nutritional experiments suggested that wild-type S. enterica uses a ligand other than DMB during growth on propanediol.…”
Section: Conditions That Prevent Synthesis or Installation Of Any ␣-Amentioning
confidence: 99%
“…It was reported that wild-type S. enterica synthesizes pseudo-B 12 during growth under strictly anaerobic conditions and standard B 12 under microaerobic conditions (21,22). Nutritional experiments suggested that wild-type S. enterica uses a ligand other than DMB during growth on propanediol.…”
Section: Conditions That Prevent Synthesis or Installation Of Any ␣-Amentioning
confidence: 99%
“…DMB synthesis in some anaerobes appears to branch from the purine biosynthetic pathway, although enzymes involved in this process have not been isolated (11,18). Interestingly, S. enterica synthesizes the corrin ring anaerobically and derives DMB aerobically from flavin mononucleotide (FMN), although no ortholog of BluB appears to exist in the genome (1,12).…”
mentioning
confidence: 99%
“…The observation that S. enterica produces B 12 [DMB], but that no DMB biosynthetic enzyme has been identified in S. enterica, has puzzled researchers for many years (23). Anderson et al explored this issue by selecting for mutants of S. enterica that grow under conditions that normally require exogenous DMB (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This facultative anaerobic enterobacterium can salvage incomplete corrinoids [e.g. cobyric acid (Cby) and cobinamide (Cbi)] from its environment and converts them into AdoCba under both aerobic and anaerobic conditions (Brushaber et al, 1998;Jeter et al, 1984;Keck et al, 1998). The resulting AdoCba functions as coenzyme for 1,2-propanediol dehydrase and ethanolamine ammonia-lyase enzymes in this bacterium, and is the source of the non-adenosylated cobamide used by methionine synthase (Babior, 1982;Taylor & Weissbach, 1973;Toraya & Fukui, 1982).…”
Section: Introductionmentioning
confidence: 99%